Quality of life change seen after Diverted Mini Gastric Bypass Surgery in Obese Population: Retrospective research analysis - Singh, Arya; Narwaria, Mahendra; Patel, Prachi; Sinha, Susmita; Ahmad, Rahnuma; Haque, Mainul; Kumar, Santosh; Sanghani, Nandita (Bangladesh Journal of Medical Science, 2023)
Background: With an increase in life expectancy all over the globe, morbid obesity and obesity-related diseases negatively impact the overall quality of life (QoL). Aim: The study aimed to assess the QoL post-Diverted Mini Gastric Bypass (dMGB), focusing on weight loss achieved, comorbidity resolution, and change in QoL after the surgery. Setting: Single private institute, India Methods : Data from patients who underwent a laparoscopic primary dMGB from August 2020 to August 2021 by one surgeon were retrospectively analyzed. The patients were followed up at 3,6,9, and 12 months from the surgery date. Data were assessed using the Bariatric Analysis and Reporting Outcome System- II (BAROS- II) form based on three major areas: percentage weight loss, comorbidity resolution, and QoL. The variation in QoL was assessed using the Moorehead Ardelt QoL questionnaire, which addresses self-esteem, physical activity, social gathering, and sexual life. Results: Forty-one patients were included in the final analysis. The average age and pre-operative body mass index (BMI) was 45.5 yrs. and 44.5 kg/m2, respectively. The cohort had 60.9% of males and 39.1% females. The pre-operative average total QoL score was 0.65 ± 0.2. At 12 months, the average BMI and average total QoL were 28.03 kg/m2 and 5.35 ± 0.3, respectively, p<0.001. Conclusion: At one year, the dMGB surgery effectively improves the overall QoL. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 759-767